2018
DOI: 10.1002/1873-3468.13278
|View full text |Cite
|
Sign up to set email alerts
|

The gut microbiome participates in transgenerational inheritance of low‐temperature responses in Drosophila melanogaster

Abstract: Environmental perturbations induce transcriptional changes, some of which may be inherited even in the absence of the initial stimulus. Previous studies have focused on transfers through the germline although microbiota is also passed on to the offspring. Thus, we inspected the involvement of the gut microbiome in transgenerational inheritance of environmental exposures in Drosophila melanogaster . We grew flies in the cold versus control temperatures and compared their transcriptional p… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

2
32
0

Year Published

2019
2019
2022
2022

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 26 publications
(34 citation statements)
references
References 38 publications
2
32
0
Order By: Relevance
“…A) to examine if the set of differentially expressed genes induced by cold and fecal transfer as reported by Zare et al . is enriched for microbiota‐induced differentially expressed genes identified in previous studies on D. melanogaster . A significant FE or FD in this analysis would indicate that the overlap between any two given gene sets is higher or lower than what is expected by chance.…”
Section: Resultsmentioning
confidence: 74%
See 4 more Smart Citations
“…A) to examine if the set of differentially expressed genes induced by cold and fecal transfer as reported by Zare et al . is enriched for microbiota‐induced differentially expressed genes identified in previous studies on D. melanogaster . A significant FE or FD in this analysis would indicate that the overlap between any two given gene sets is higher or lower than what is expected by chance.…”
Section: Resultsmentioning
confidence: 74%
“…Labels originally used in ref. are indicated in parentheses. Labels used here to represent different microbiota studies are also similarly indicated.…”
Section: Methodsmentioning
confidence: 99%
See 3 more Smart Citations